2008
DOI: 10.1002/sia.2695
|View full text |Cite
|
Sign up to set email alerts
|

Mg‐Fe‐hydrotalcite as catalyst for the benzylation of benzene and other aromatics by benzyl chloride reactions

Abstract: The benzylation of benzene and substituted benzenes reaction employing benzyl chloride as the alkylating agent over Mg-Fe-LDH (Mg/Fe = 2) clay without or with calcination (at 473-1073 K) has been investigated. Hydrotalcite before and after its calcination was characterized for surface area and crystalline phases. The catalyst derived from the hydrotalcite by its calcination at 473-1073 K show high catalytic activity for the benzylation of benzene and other aromatic compounds. The catalytically active species p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…However, the substitution of liquid acids by solid acid catalysts is a challenging task. 12 Efforts have been directed towards designing of efficient solid acid catalysts such as metal and metal oxide supported mesoporous and microporous materials. [13][14][15][16][17][18][19][20][21][22] Recently, it has been shown that Ga 2 O 3 supported on MCM-41 is very active for Friedel-Crafts type benzylation and acylation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the substitution of liquid acids by solid acid catalysts is a challenging task. 12 Efforts have been directed towards designing of efficient solid acid catalysts such as metal and metal oxide supported mesoporous and microporous materials. [13][14][15][16][17][18][19][20][21][22] Recently, it has been shown that Ga 2 O 3 supported on MCM-41 is very active for Friedel-Crafts type benzylation and acylation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…From the multitude of Me 2+ /Me 3+ LDH types, much focus has been directed toward the Mg 2+ /Fe 3+ pair. A literature search revealed that Mg/Fe-LDH has been used for phosphate removal from aqueous solutions [9][10][11]; as adsorbent materials of various heavy metals, such as Cr, As, Pb, Zn, Cu, Se, Sb, and so forth [12][13][14][15][16]; for treatment of aqueous solutions contaminated with different reactive dyes [17][18][19]; or as a catalyst [20][21][22]. Presently, there is a focus on obtaining cheaper adsorbent materials that still retain properties similar to those obtained from pure chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Three probable mechanistic interpretations can be found in the literature for benzylation of aromatic hydrocarbons with benzyl chloride on solid acid based supported metal catalysts, without any direct (preparative or spectroscopic) experimental verification: a simple radical step [12][13][14][15][16][17] -see Scheme 1; the presence of a benzyl chloride radical cation [4,[18][19][20][21][22][23][24][25]] -see Scheme 2; or the presence of a benzyl radical cation [26][27][28] as intermediate -see Scheme 3. In some cases the same authors have different suggestions for similar catalytic systems.…”
Section: Introductionmentioning
confidence: 99%